2015
DOI: 10.1002/bmc.3544
|View full text |Cite
|
Sign up to set email alerts
|

Ion pair liquid chromatography method for the determination of thiamine (vitamin B1) homeostasis

Abstract: A new method for reversed phase HPLC determination of thiamine and its major in vivo phosphorylation products, thiamine monophosphate (TMP) and thiamine pyrophosphate (TPP), was developed using tetrabutylammonium hydroxide as the ion-pairing agent. The separation was performed on a Phenomenex Kinetex EVO C18 column with a gradient of a phosphate-buffered aqueous solution of the ion-pair reagent and methanol. The duty cycle for the assay was 13 min and pyrithiamine was successfully used as the internal standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…A survey of participants enrolled in the RCPAQAP whole-blood programme revealed that only one of nine respondents included an internal standard [22]. Furthermore, from our literature search, only four publications reported the use of an internal standard [109,125,128,129].…”
Section: Quality Goalsmentioning
confidence: 98%
See 2 more Smart Citations
“…A survey of participants enrolled in the RCPAQAP whole-blood programme revealed that only one of nine respondents included an internal standard [22]. Furthermore, from our literature search, only four publications reported the use of an internal standard [109,125,128,129].…”
Section: Quality Goalsmentioning
confidence: 98%
“…Separation can be accomplished using gradient or isocratic techniques, with or without ion-pairing chemicals and on a range of columns including octadecyl carbon chain silica based (C 18 ), polymer, or amino. Sample preparation procedures include cloud point extraction (using the cloud phenomena of surfactants), solid phase extraction and derivitisation (which can occur pre-or post-column) [112,[127][128][129]. There are also an array of mobile phase solutions and chemicals for sample preparation with variations in pH levels from 2 to 13, even when identical chemicals are utilised.…”
Section: Direct Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, all samples were injected into the chromatographic system within 1 min. Comparing to data obtained by other study, 30 min can be considered a lower stability [41]. They found that TDP, TMP and B1 kept in a cell culture after derivatization were stable until 3 h, at room temperature.…”
Section: Assay Validationmentioning
confidence: 65%
“…One possible explanation for the difference between these results could be not only the kind of samples, cells and tissues, but also light effects on the compound stability. The derivatized samples were stored in the dark at room temperature [41]. Further systematic studies have to be done to test this hypothesis.…”
Section: Assay Validationmentioning
confidence: 99%